Meningkatkan Hasil Belajar Pak Siswa Kelas VII Melalui Penggunaan Model PBL SMP Negeri 2 Harian Pada Materi Aku Memiliki Kemampuan - Iten Rosalina Sihotang; Yohanes Umbu Lede; Paulus Asriadi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of grade VII students on the material "I Have the Ability" through the application of the Problem-Based Learning (PBL) model at SMP Negeri 2 Harian in the 2024/2025 academic year. The PBL method was chosen because of its ability to increase student engagement, critical thinking skills, and problem solving that is relevant to everyday life. This study uses a classroom action research (CAR) design involving two cycles of action. Data were collected through learning outcome tests, observations of the learning process, and evaluation questionnaires. The results showed a significant increase in student learning outcomes, as indicated by an increase in test scores and positive feedback from students regarding the learning process. The application of the PBL model also showed an increase in collaboration skills and student learning motivation. Thus, the use of the Problem-Based Learning model can be considered effective in improving student learning outcomes on the material taught.